PENANAMAN MORINGA OLEIFERA UNTUK PENINGKATAN KESEHATAN MASYARAKAT DAN PENGHIJAUAN DI DUSUN TAMBAK REJO MOJOKERTO: MORINGA OLEIFERA PLANTING FOR IMPROVING COMMUNITY HEALTH AND GREENING IN TAMBAK REJO VILLAGE MOJOKERTO DISTRICT - Tri Peni; Tri Ratnaningsih; Siti Indatul Laili (Jurnal Pengabdian Masyarakat Kesehatan, 2020)
ABSTRACT Tambak Rejo Village has a fairly arid area in the dry season and in areas that are flooded by rivers experiencing flooding in the rainy season. In the dry season the conditions of the settlement are hot because few plants can grow. Only certain plants can flourish in the area. Moringa plants are plants that are easy to plant and also have very good endurance in the event of seasonal changes. Moringa plants which have the Latin name Moringa oleifera can grow up to 7 meters high or even 12 meters tall. Moringa tree in addition to greening on arid land, has many benefits in the field of health both leaves, bark or fruit and seeds. The leaves can be made into useful vegetables to increase endurance and improve the digestive system. The procedure of this community service activity starts from the team coordinating with partners. The implementation begins with coordination with partners to determine the schedule of activities. The socialization of the benefits of moringa oleifera was carried out in Tambak Rejo Village, attended by 68 residents. After the socialization continued with the distribution of Moringa oleifera seeds to the people who attended. The team gave examples of planting and monitored the process of planting moringa oleifera in Tambak Rejo Village. The results of the evaluation of Moringa oleifera plants grow well and are well groomed. Residents have used the leaves for consumption as a daily vegetable menu. The targets of community service are greening on arid land and the use of moringa oleifera to improve public health.